Measurement of the t(t)over-bar production cross section in the e mu channel in proton-proton collisions at root s=7 and 8 TeV - (:unkn) unknown (SPRINGER, 2016)
The inclusive cross section for top quark pair production is measured in proton-proton collisions at root s = 7 and 8TeV, corresponding to 5.0 and 19.7 fb(-1), respectively, with the CMS experiment at the LHC. The cross sections are measured in the electron-muon channel using a binned likelihood fit to multi-differential final state distributions related to identified b quark jets and other jets in the event. The measured cross section values are 173.6 +/- 2.1 (stat)(-4.0)(+ 4.5)(syst) +/- 3.8 (lumi) pb at root s = 7TeV, and 244.9 +/- 1.4(stat)(-5.5)(+6.3) (syst) +/- 6.4 (lumi) pb at root s = 8TeV, in good agreement with QCD calculations at next-to-nextto- leading-order accuracy. The ratio of the cross sections measured at 7 and 8TeV is determined, as well as cross sections in the fiducial regions defined by the acceptance requirements on the two charged leptons in the final state. The cross section results are used to determine the top quark pole mass via the dependence of the theoretically predicted cross section on the mass, giving a best result of 173.8(-1.8)(+1.7) GeV. The data at root s = 8TeV are also used to set limits, for two neutralino mass values, on the pair production of supersymmetric partners of the top quark with masses close to the top quark mass.
Keywords: Hadron-Hadron scattering (experiments); Top physics; PARTON DISTRIBUTIONS; HADRON COLLIDER; PAIR PRODUCTION; PP COLLISIONS; DARK-MATTER; SQUARK; EVENT